Implementing sensor‐based digital health technologies in clinical trials: Key considerations from the eCOA Consortium - Elena S. Izmailova; Danielle Middleton; Reem Yunis; Julia Lakeland; Kristen Sowalsky; Julia Kling; Alison Ritchie; Christine C. Guo; Bill Byrom; Scottie Kern (Wiley, 2024)
Abstract The increased use of sensor‐based digital health technologies (DHTs) in clinical trials brought to light concerns about implementation practices that might introduce burden on trial participants, resulting in suboptimal compliance and become an additional complicating factor in clinical trial conduct. These concerns may contribute to the lower‐than‐anticipated uptake of DHT deployment and data use for regulatory decision‐making, despite well‐articulated benefits. The Electronic Clinical Outcome Assessment (eCOA) Consortium gathered collective experience on deploying sensor‐based DHTs and supplemented this with relevant literature focusing on mechanisms that may enhance participant compliance. The process for DHT implementation starts with identifying a clinical concept of interest followed by a digital measure selection, defining active or passive data capture and their sources, the number of sensors with respective body location, plus the duration and frequency of use in the context of perceived participant burden. Roundtable discussions among patient groups, physicians, and technology providers prior to protocol development can be very impactful for optimizing trial design. While diversity and inclusion are essential for any clinical trial, patient populations should be considered carefully in the context of trial‐specific aims, requirements, and anticipated patient burden. Minimizing site burden includes assessment of training, research engagement, and logistical burden which needs to be triaged differently for early and late‐stage clinical trials. Additional considerations include sharing trial results with study participants and leveraging publicly available data for compliance modeling. To the best of our knowledge, this report provides holistic considerations for sensor‐based DHT implementation that may optimize participant compliance.